2020
DOI: 10.1002/cplu.202000471
|View full text |Cite
|
Sign up to set email alerts
|

Acrylic Polymers Containing a Nickel Salphen Complex: An Approach to Supramolecular and Macromolecular Systems

Abstract: The synthesis, characterization and crystallographic analysis is reported of a new Nickel Salphen complex and its radical copolymerization with n-butyl acrylate and methyl methacrylate to produce novel host macromolecules with tunable association against guest anions. Spectrophotometric titrations of the complex and of the polymers revealed that a supramolecular regulation of guest-binding accessibility was enabled by the number of Ni-Salphen units per chain. The latter content in turn, determined the chain si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Previous reports on copolymers integrated by minor compositions of one monomer and a major composition of a different monomer that occupied larger regions in the chains demonstrated that even subtle compositional variations rendered strong supramolecular effects that proceeded cooperatively. In these cases, the chain domains occupied by the major component in the macromolecule showed a strong susceptibility to conformational alterations produced by supramolecular contributions from the minor components to the rest of the structure [40,49] . Thus, we could assume a similar contribution from the Cu−Salphen monomer to the overall chain conformation not only in the solid state, but also in suitable solutions.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Previous reports on copolymers integrated by minor compositions of one monomer and a major composition of a different monomer that occupied larger regions in the chains demonstrated that even subtle compositional variations rendered strong supramolecular effects that proceeded cooperatively. In these cases, the chain domains occupied by the major component in the macromolecule showed a strong susceptibility to conformational alterations produced by supramolecular contributions from the minor components to the rest of the structure [40,49] . Thus, we could assume a similar contribution from the Cu−Salphen monomer to the overall chain conformation not only in the solid state, but also in suitable solutions.…”
Section: Resultsmentioning
confidence: 94%
“…[53] Complex 1 and polymers 2 and 3 were synthesized following previously reported methodologies with some modifications. [37,40,43] TGA experiments were carried out under 2 flow at 10 °C min À 1 on a Perkin Elmer TGA4000 apparatus; T i = 30 °C, T f = 460 °C. DSC data was achieved under N 2 at 10 °C min À 1 on a Mettler Toledo DSC1 calorimeter at Unidad de Servicios de Apoyo a la Investigación y a la Industria (USAII) of the School of Chemistry-UNAM; conditioning cycles: 1) r.t. to 100 °C, 2) isothermal at 100 °C for 10 min, 3) 100 °C to À 100 °C, 4) isothermal at À 100 °C for 10 min; measurement cycle: 5) À 100 °C to 250 °C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations